PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN FLASHCARD DIGITAL TERHADAP PENINGKATAN PENGUASAAN KOSAKATA BAHASA INGGRIS SISWA KELAS III DI SEKOLAH DASAR - Nurul Maftukhtail A; Riris Setyo Sundari; Bagus Ardi Saputro (STKIP Subang, 2025)
This study aims to determine the effect of using digital flashcards on the English vocabulary mastery of third-grade elementary school students. The main issue addressed is the low level of vocabulary mastery caused by learning methods that are less engaging. The research employed a quantitative approach with a One Group Pretest–Posttest design. Data were collected through tests administered before and after the treatment, then analyzed to identify changes in students’ abilities. The findings show that digital flashcards have a positive impact on improving vocabulary mastery. This media is effective because it provides interactive and engaging learning experiences that align with the needs of elementary learners. Therefore, digital flashcards can be used as an alternative instructional media to enhance students’ English vocabulary mastery.